Wakaf dalam Perspektif Al-Qur’an dan Hadis: Esensi dan Signifikansi pada Tataran Ekonomi dan Sosial - Ade Nur Rohim; Ahmad Hasan Ridwan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Waqf in the Perspective of the Qur'an and Hadith: Essence and Significance at the Economic and Social LevelWaqf is a form of Islamic philanthropy that has received significant attention both in the Qur'an and Hadith. Various arguments related to waqf, both from the Qur'an and Hadith, have shown many suggestions and wisdom for waqf. Nevertheless, it is necessary to synthesize the essence of the interrelationships of the various existing propositions focused on the economic and social aspects. This article aims to review the essence of the concept of waqf from the perspective of the Qur'an and Hadith which is elaborated by reviewing its significance at the economic and social levels. This study uses a qualitative research method with a literature study approach. The results of this study describe the concept of waqf and its essence is reflected in several verses of the Qur'an which are the basis for waqf sharia, as well as various waqf practices by the Prophet Muhammad. and the companions recorded in the Hadith. In addition, this study also finds that with this essence, waqf has a direct contribution to individual development as a form of shadaqah jariyah, besides waqf is also an instrument of income redistribution and an instrument of development financing